Discrimination of MSA-P and MSA-C by RT-QuIC analysis of olfactory mucosa: the first assessment of assay reproducibility between two specialized laboratories - Bargar, Connor; De Luca, Chiara Maria Giulia; Devigili, Grazia; Elia, Antonio Emanuele; Cilia, Roberto; Portaleone, Sara Maria; Wang, Wen; Tramacere, Irene; Bistaffa, Edoardo; Cazzaniga, Federico Angelo; Felisati, Giovanni; Legname, Giuseppe; et al. (Molecular neurodegeneration, 2021)
Background Detection of the pathological and disease-associated alpha-synuclein (αSyn D ) in the brain is required to formulate the definitive diagnosis of multiple system atrophy (MSA) and Parkinson’s disease (PD). We recently showed that αSyn D can be detected in the olfactory mucosa (OM) of MSA and PD patients. For this reason, we have performed the first interlaboratory study based on α-synuclein Real-Time Quaking-Induced Conversion (αSyn_RT-QuIC) analysis of OM samples collected from PD and MSA patients with the parkinsonian (MSA-P) and cerebellar (MSA-C) phenotypes. Methods OM samples were prospectively collected from patients with a probable diagnosis of MSA-P ( n = 20, mean disease duration 4.4 years), MSA-C ( n = 10, mean disease duration 4 years), PD ( n = 13, mean disease duration 8 years), and healthy control subjects (HS) ( n = 11). Each sample was analyzed by αSyn_RT-QuIC in two independent specialized laboratories, one located in Italy (ITA-lab) and one located in the USA (USA-lab). Both laboratories have developed and used harmonized αSyn_RT-QuIC analytical procedures. Results were correlated with demographic and clinical data. Results The αSyn_RT-QuIC analysis reached a 96% interrater agreement of results (IAR) between laboratories (Kappa = 0.93, 95% CI 0.83–1.00). In particular, αSyn_RT-QuIC seeding activity was found in the OM of 9/13 patients with PD (sensitivity 69%, IAR 100%) and 18/20 patients with MSA-P (sensitivity 90%, IAR 100%). Interestingly, samples collected from patients with MSA-C did not induce αSyn_RT-QuIC seeding activity, except for one subject in USA-lab. Therefore, we found that MSA-P and MSA-C induced opposite effects. Regardless of disease diagnosis, the αSyn_RT-QuIC seeding activity correlated with some clinical parameters, including the rigidity and postural instability. Conclusions Our study provides evidence that OM-αSyn D may serve as a novel biomarker for accurate clinical diagnoses of PD, MSA-P, and MSA-C. Moreover, αSyn_RT-QuIC represents a reliable assay that can distinguish patients with MSA-P from those with MSA-C, and may lead to significant advancements in patients stratification and selection for emerging pharmacological treatments and clinical trials.